Prescribing high-intensity interval exercise by rating of perceived exertion in young individuals - Marçal, Isabela R. [UNESP]; Falqueiro, Pedro G. [UNESP]; Fernandes, Bianca [UNESP]; Ngomane, Awassi Y. [UNESP]; Amaral, Vanessa T. [UNESP]; Guimarães, Guilherme V.; Ciolac, Emmanuel G. [UNESP] (Edizioni Minerva Medica, 2021)
Background: We tested the hypothesis that the 6 to 20 rating of perceived exertion (RPE) is a cost-effective tool similar to heart rate (HR) response to cardiopulmonary exercise test for prescribing and self-regulating high-intensity interval exercise (HIIE). In this context, we analyzed if health-related responses to exercise are similar between HIIE prescribed and self-regulated by RPE (HIIERPE) and HIIE prescribed and regulated by HR response to cardiopulmonary exercise test (HIIEHR). Methods: Twelve young (21±2 years) sedentary or insufficiently active individuals (weekly levels ˂150 minutes or 75 minutes of moderate- or vigorous-intensity physical activity, respectively) were randomly assigned to perform HIIERPE (25 minutes), HIIEHR (25 minutes) and control session (25 minutes of seated resting). Blood pressure, HR, and arterial stiffness (pulse wave velocity) were measured before, immediately after, and 30 minutes after each intervention. HR, speed, and distance were measured during exercise sessions. 24-hours ambulatory blood pressure was measured after each intervention. Results: Exercise HR, speed, and distance, as well as blood pressure response to exercise were not different between HIIERPE and HIIEHR. Pulse wave velocity reduced (P<0.05) at postintervention in both HIIERPE (0.28±0.17 m/s) and HIIEHR (0.27±0.11 m/s). However, pulse wave velocity at recovery was lower than pre-intervention only during HIIERPE (0.30±0.10 m/s). Conclusions: These results suggest that RPE is a cost-effective tool for prescribing self-regulating HIIE and improving health-related variables in young individuals.
Keywords: Blood pressure; High-intensity interval training; Vascular stiffness